Electronic and optical performances of (Cu, N) codoped TiO2/g-C3N4 heterostructure photocatalyst: A spin-polarized DFT + U study. (1st March 2018) - Zhao, Yali; Lin, Yanming; Wang, Guanshi; Jiang, Zhenyi; Zhang, Ruiqin; Zhu, Chaoyuan
Graphical abstract: Highlights: Bandgap of TiO2 /g-C3 N4 has an obvious narrowing compared with TiO2 (1 0 1) surface. Cu&N codoping induces the hybridized states appearing in the bandgap of TiO2 /g-C3 N4 . Interfacial coupling of TiO2 &g-C3 N4 reduces the recombination of electron-hole pairs. Cu&N codoped TiO2 /g-C3 N4 heterostructure is a satisfactory visible-light photocatalyst. Abstract: The geometrical, electronic and optical properties of Cu or/and N (co)doped TiO2 /g-C3 N4 heterostructure systems have been investigated systematically on the basis of spin-polarized density functional theory calculations. Our calculated results indicate that the band gap of TiO2 /g-C3 N4 heterostructure has an obvious narrowing compared with pure TiO2 (1 0 1) surface, and (Cu, N) codoping can induce some impurity states of N 2 p and hybridized states of Cu 3 d and N 2 p appearing in the forbidden gap of TiO2 /g-C3 N4 heterostructure, which lead to a decrease of the photon excitation energy and an obvious redshift of the optical absorption edge. Moreover, the charge density difference calculations of Cu or/and N (co)doped TiO2 /g-C3 N4 heterostructure systems show that the excited electrons and holes will eventually accumulate in (co)doping TiO2 (1 0 1) surface and g-C3 N4 monolayer, respectively, which can effectively reduce the recombination of the photogenerated electron-hole pairs by the interfacial coupling of between TiO2 (1 0 1) surface and g-C3 N4 monolayer. This work not only investigates systematically the electronic and optical properties of Cu or/and N (co)doped TiO2 /g-C3 N4 heterostructure, but also suggests that (Cu, N) codoped TiO2 /g-C3 N4 heterostructure is a preferable visible-light photocatalyst.